APPLICATION OF LM 35 TEMPERATURE SENSOR FOR SEAWATER DISTILLATION - Saukani, Imam; Triturani, Rina (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2022)
Indonesia is an archipelago, so many settlements close to the beach or sea. People living in the area are still many who lack clean water. One way to get clean water is sea water by distillation. Distillation is a liquid changes into steam and the steam is cooled back into a liquid. The process of designing and manufacturing distillation in this paper serves to make sea water into fresh water and also to stabilize the temperature during heating. Given these problems required temperature control system. Application of fuzzy logic controllers are expected to solve the problem of temperature stability in sea water distillation equipment. The sensor used is LM 35 sensors as readers seawater temperature is used as a reference to maintain a temperature in the range of 80° -100°C. Fuzzy logic rules are applied has a 9, which is obtained from the membership functions of 3 error and 3 delta error membership functions. Application of Fuzzy Logic Controller When the set point temperature of 85°C temperature response curve is obtained which has a performance controller Error Steady-state = 0.35%, Max Overshoot = 0, settling time = 103 minutes, peak time = 0, rise time = 37 minutes. With the set point of 75°C -99°C then obtained a qualified water quality water temperature of 100°C is worth to drink and has a good time efficiency for distillation temperature.